2018
DOI: 10.1111/agec.12423
|View full text |Cite
|
Sign up to set email alerts
|

The components of the bid‐ask spread: Evidence from the corn futures market

Abstract: This article examines whether USDA announcements and commodity index fund rolling activity have an impact on liquidity costs, measured by the bid-ask spread. Using Huang and Stoll's (1997) model of liquidity costs, we estimate whether changes to liquidity costs are driven by its adverse selection, inventory, or order processing components. Commodity index fund roll activity reduces the asymmetric information cost component of liquidity cost due to an increased proportion of noninformation-based trading, but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…However, the magnitude and significance of the parameter decreases from 3.9% in the first contract pair to 3.6% in the second contract pair and becomes insignificant in the third and fourth contract pairs. Several studies have documented a “sunshine trading effect,” which consists of a predetermined commodity index roll period attracting counterparties and increasing liquidity supply (Shang, Mallory, & Garcia, 2018). Since traders are highly concentrated in the nearby contract during index rolling periods (Aulerich, Irwin, & Garcia, 2014), one possible explanation for the positive correlation between index rolling and PS could be that liquidity improvement caused by the “sunshine trading effect” is more pronounced in nearby contracts than deferred contracts.…”
Section: Resultsmentioning
confidence: 99%
“…However, the magnitude and significance of the parameter decreases from 3.9% in the first contract pair to 3.6% in the second contract pair and becomes insignificant in the third and fourth contract pairs. Several studies have documented a “sunshine trading effect,” which consists of a predetermined commodity index roll period attracting counterparties and increasing liquidity supply (Shang, Mallory, & Garcia, 2018). Since traders are highly concentrated in the nearby contract during index rolling periods (Aulerich, Irwin, & Garcia, 2014), one possible explanation for the positive correlation between index rolling and PS could be that liquidity improvement caused by the “sunshine trading effect” is more pronounced in nearby contracts than deferred contracts.…”
Section: Resultsmentioning
confidence: 99%
“…Shang et al. (2018) show that market volatility and BAS are relatively high during the market open, a period when the volume is usually elevated, and the risk to liquidity providers due to adverse selection is high. Similar to findings in the literature, we find increased trading volume, volatility, and relative spread during market opening and closing.…”
Section: Resultsmentioning
confidence: 99%
“…Existing studies have also identified that market conditions vary during trading hours. For example, trading activity and volatility are generally higher during market opening and closing than during mid‐day hours (Joseph & Garcia, 2018; Shang et al., 2018), which is likely to affect market quality. To capture these intraday patterns, we introduce dummy variables for the first (last) 30 minutes of market opening (closing), Opn (Cls).…”
Section: Hlo Impacts On Market Qualitymentioning
confidence: 99%
“…On each trading day, about 10–20 maturities are traded with different levels of activity. We focus on the nearby contracts as they are the most liquid, which should allow for a more accurate assessment of the market response to USDA announcements (Isengildina‐Massa et al., ; Karali, ; Shang et al., ). Each contract is rolled over to the second‐nearby contract when the volume of the second‐nearby contract exceeds the volume of the front‐end contract.…”
Section: Datamentioning
confidence: 99%
“…Shang et al. () focus on the impact of commodity index fund roll activity and USDA announcements on liquidity costs on the day following the announcement.…”
mentioning
confidence: 99%